PENERAPAN MANAJEMEN SUMBER DAYA MANUSI SYARIAH DI HOTEL GRASIA - Fikri, Fajar Muhammad; Yuniawan, Ahyar (JURNAL BISNIS STRATEGI, 2016)
The purpose of this research is to know how the application of Human Resources Management in Hotel Grasia Semarang, whether it is appropriate with Islamic values by looking the practical management of Hotel Grasia.This research use qualitative method where is the data collection conducted by interview and deeply observation for a certain period to get more information about the application of Human Resources Management based on Islamic values. The object of this research is a Hotel which is proceeded in syariah system, that is Hotel Grasia Semarang. Then the Informant in this research are the employees of this Hotel who have worked for more than 5 years.The result shot the outline of Islamic values which are still maintained and applicated practically in Human Resources Management in Hotel Grasia Semarang. The Islamic values are showed by several criterias, test or material in some management practices. The spiritual side is also looked from the employees participation in several religious events that showed the religious side of the person.Â